The advanced care coordination program: a protocol for improving transitions of care for dual-use veterans from community emergency departments back to the Veterans Health Administration (VA) primary care - Lindsay B. Miller; Heidi Sjoberg; Ashlea Mayberry; Marina S. McCreight; Roman A. Ayele; Catherine Battaglia (BMC, 2019)
Abstract Background Veterans who access both the Veterans Health Administration (VA) and non-VA health care systems require effective care coordination to avoid adverse health care outcomes. These dual-use Veterans have diverse and complex needs. Gaps in transitions of care between VA and non-VA systems are common. The Advanced Care Coordination (ACC) quality improvement program aims to address these gaps by implementing a comprehensive longitudinal care coordination intervention with a focus on Veterans' social determinants of health (SDOH) to facilitate Veterans' transitions of care back to the Eastern Colorado Health Care System (ECHCS) for follow-up care. Methods The ACC program is an ongoing quality improvement study that will enroll dual-use Veterans after discharge from non-VA emergency department (EDs), and will provide Veterans with social worker-led longitudinal care coordination addressing SDOH and providing linkage to resources. The ACC social worker will complete biopsychosocial assessments to identify Veteran needs, conduct regular in-person and phone visits, and connect Veterans back to their VA care teams. We will identify non-VA EDs in the Denver, Colorado metro area that will provide the most effective partnership based on location and Veteran need. Veterans will be enrolled into the ACC program when they visit one of our selected non-VA EDs without being hospitalized. We will develop a program database to allow for continuous evaluation. Continuing education and outreach including the development of a resource guide, Veteran Care Cards, and program newsletters will generate program buy-in and bridge communication. We will evaluate our program using the Reach, Effectiveness, Adoption, Implementation, and Maintenance framework, supported by the Practical, Robust Implementation and Sustainability Model, Theoretical Domains Framework, and process mapping. Discussion The ACC program will improve care coordination for dual-use Veterans by implementing social-work led longitudinal care coordination addressing Veterans' SDOH. This intervention will provide an essential service for effective care coordination.